EVALUASI KONDISI VEGETASI DAN VISUALISASI STRUKTUR TEGAKAN PADA AREAL REVEGETASI BLOK TAMBANG SELATAN PT. ANTAM TBK UPB NIKEL POMALAA - Zulkarnain Zulkarnain (Jurnal Ecogreen, 2016)
This study aims to evaluating plant growth from revegetation activity results, and visualize the structure stands in the study area.  The research was conducted at the revegetation site of the South mine block  of  PT. ANTAM Tbk UPB Pomalaa, district Kolaka, Southeast Sulawesi, since january to december 2013.  This study uses survey method, determining the location of sampling using purposive sampling and shape of sample plots are terraced lines.  The variables of this study is the number of species, species density and diversity of species.  The data were analyzed using quantitative descriptive analysis.  sexi-FS software is used to get a visualization of the distribution of vegetation and  stratification of canopy that similar with the field situations.  The results showed that an increasing number of species on the level of vegetation trees and saplings.  While at the level of the pole number of species encountered are the same as the previous monitoring period.  As in the seedling stage noticeable decrease in the number of types.  Vegetation density increased in the group of trees and poles, while the density of saplings decline though not significantly.  The level of diversity showed significant improvements at the tree level, while at other levels decreased quantity though not significantly.  The spread of vegetation indicates a uniform distribution pattern (uniform).  Stratification headers are composed mainly of at most 3 stratum, that is  C, D and E, even some are only composed by two strata only, that is  D and E. This shows that, overall, the plant community is still in the process of growth to reach climax.Key Words ;  Revegetation, Vegetation analysis, Visualization stand structure,  PT. Antam,Tbk.